Why critical literacy should turn to 'the affective turn': making a case for critical affective literacy. Issue 3 (3rd May 2016) - Anwaruddin, Sardar M.
Abstract : The central argument of this essay is that critical literacy with a rationalistic bent may not enable us to cope with ethical dilemmas in our responsiveness to human sufferings. I argue that critical literacy education would benefit from turning to the recent scholarship on affect/emotion studies. I draw upon the works of Sara Ahmed – one of the leading contributors to critical affect studies – to shed light on what is called a regulatory power that creates a schism in our responsiveness to violence and suffering. The key contribution of this essay is to present an actionable framework of what I describe as critical affective literacy. To delineate this framework, I present four pedagogical principles, along with examples of instructional activities.